Cervical adenocarcinoma presenting as an ovarian torsion - M. Mvula; S. Roychoudhury; K. King; N. Aravindan; C. Chan; V. John; J. Whyte; GL. Goldberg (Gynecologic Oncology Reports, 2024)
Background: Cervical adenocarcinoma is increasing in incidence and can rarely present as ovarian metastasis.Case: A 41-year-old female who presented with left lower quadrant pain and vomiting. Intra-operative findings revealed bilateral ovarian cysts with initial pathology results of mucinous ovarian adenocarcinoma. Final histopathology revealed an invasive poorly differentiated mucinous adenocarcinoma of the cervix. Conclusions: Mucinous adenocarcinoma in the ovary is usually a metastasis and an extensive and comprehensive work-up is required to try to locate the primary tumor.Précis: Mucinous adenocarcinoma in the ovary is usually a metastasis and an extensive and comprehensive work-up is required to try to locate the primary tumor.